2021
DOI: 10.1371/journal.pone.0260792
|View full text |Cite
|
Sign up to set email alerts
|

Divergence together with microbes: A comparative study of the associated microbiomes in the closely related Littorina species

Abstract: Any multicellular organism during its life is involved in relatively stable interactions with microorganisms. The organism and its microbiome make up a holobiont, possessing a unique set of characteristics and evolving as a whole system. This study aimed to evaluate the degree of the conservativeness of microbiomes associated with intertidal gastropods. We studied the composition and the geographic and phylogenetic variability of the gut and body surface microbiomes of five closely related sympatric Littorina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 107 publications
(112 reference statements)
5
11
0
Order By: Relevance
“…The present study was conducted at the local scale and there were no significant differences between sites that were only few km apart. There was a clear separation between the environmental microbiomes and the bacteria associated with the snail host, which agrees with the recent finding for the Pacific L. keenae (Neu et al, 2019) and several Atlantic Littorina species (Maltseva et al, 2021). Similar to the studies above we found some bacterial families exclusively associated with the snail host but the majorities of differences were at the abundance level.…”
Section: Environmental and Snail-associated Microbiomessupporting
confidence: 92%
See 3 more Smart Citations
“…The present study was conducted at the local scale and there were no significant differences between sites that were only few km apart. There was a clear separation between the environmental microbiomes and the bacteria associated with the snail host, which agrees with the recent finding for the Pacific L. keenae (Neu et al, 2019) and several Atlantic Littorina species (Maltseva et al, 2021). Similar to the studies above we found some bacterial families exclusively associated with the snail host but the majorities of differences were at the abundance level.…”
Section: Environmental and Snail-associated Microbiomessupporting
confidence: 92%
“…There were some differences between the bacterial communities in the biofilm on the boulder beaches and lower and upper parts of the cliffs, in agreement with other studies on intertidal zonation of microbial communities (Arboleda-Baena et al, 2021;Weigel & Erwin, 2017). In the previous study we found regional differences in the intertidal microbiomes between Norway and Sweden (Maltseva et al, 2021). The present study was conducted at the local scale and there were no significant differences between sites that were only few km apart.…”
Section: Environmental and Snail-associated Microbiomessupporting
confidence: 92%
See 2 more Smart Citations
“…Among invertebrates, mollusks stand out as ecologically significant and diverse phyla, being Gastropoda the richest class regarding species diversity (Neu et al 2019). Although descriptions of marine gastropod microbiota are accumulating, they mainly focus on commercial and/or northern hemisphere species, excluding most gastropod diversity (Neu et al 2019;Maltseva et al 2021b;Panova et al 2022). Moreover, the contribution of host diversification in shaping gastropod microbiota assembly remains largely unexplored.…”
Section: Resultsmentioning
confidence: 99%